S = 12 + ( – 91 ) + 188 + ( – 9 ) + 400 T = ( – 2019 ) + 100 + ( – 81 ) + 2000

S = 12 + ( – 91 ) + 188 + ( – 9 ) + 400
T = ( – 2019 ) + 100 + ( – 81 ) + 2000

2 bình luận về “S = 12 + ( – 91 ) + 188 + ( – 9 ) + 400 T = ( – 2019 ) + 100 + ( – 81 ) + 2000”

  1. Giải đáp+Lời giải và giải thích chi tiết:
    S = 12 + ( – 91 ) + 188 + ( – 9 ) + 400
       = ( 12 + 188 + 400 ) +  [ ( – 91 ) + ( – 9 ) ]
       = 600 + ( – 100 ) 
       = 600 – 100
       = 500
    T = ( – 2019 ) + 100 + ( – 81 ) + 2000
       = [ ( – 2019 ) + ( – 81 ) ] + ( 100 + 2000 )
       = – 2100 + 2100
       = 0

    Trả lời
  2. S = 12 + ( – 91 ) + 188 + ( – 9 ) + 400
       = (12 + 188) + 400 – (91 + 9)
       = 200 + 400 – 100
        = 600 – 100
        = 500
    Vậy S = 500
    ———
    T = ( – 2019 ) + 100 + ( – 81 ) + 2000
       = (2000 + 100) – (81 + 2019)
       = 2100 – 2100
       = 0
    Vậy T = 0
    ———
    color{cyan}{@SunDayy}

    Trả lời

Viết một bình luận

Câu hỏi mới